Fighting corruption and individual guarantees (Euro-Latin American Journal of Administrative Law, 2023)
This article aims to assess how the fight against corruption can affect individual guarantees. The methodology used is the bibliographic survey, which allowed the analysis of different perspectives on the subject. The results show that, in some cases, the fight against corruption can lead to a state of judicial exception, where individual guarantees are violated in the name of the fight against corruption. In addition, in some situations it can be considered lawfare, which is the use of the legal system as a political weapon, also a form of violation of individual guarantees in the context of combating corruption. Thus, the article concludes that it is important that the fight against corruption is carried out in a fair and balanced way, guaranteeing individual freedoms and democracy.
Keywords: corruption; individual guarantees; state of exception; lawfare; state.